Physico-chemical and Geochemical Correlation Study of Aliphatic Hydrocarbons for Sindh Basin (Pakistan) Condensate Samples - Zulfiqar, M.A.; Zahid, M.; Fazeelat, T. (Asian Journal of Chemistry, 2013)
Various condensate samples (Ali-1, Bilal-1, Bilal North-1 and Naimat Basal-1) are obtained from Lower Goru formation (Cretaceous) of Sindh basin (Pakistan). A molecular study for saturated/aliphatic hydrocarbons, isolated from these samples, is carried out in order to investigate genetic relationship among the samples. Moreover, physico-chemical analyses are also carried out by using ASTM methods. All the condensates show almost similar physico-chemical characteristics. These samples also show close resemblance in terms of molecular parameters. Therefore, they are suggested to share similar source. Some observed variations in physico-chemical and geochemical properties for Ali-1 compared to other condensate samples are interpreted in terms of maturity difference.